DURASI NARATIF PADA NOVEL MERINDU BAGINDA NABI KARYA HABIBURRAHMAN EL SHIRAZY (KAJIAN NARATOLOGI) - Rahayu, Titin; Supratno, Haris; Raharjo, Resdianto Permata (Jurnal Pena Indonesia, 2020)
This study aims to describe the pattern of narrative structure of the novel Merindu Baginda Nabi by Habiburrahman El Shirazy. The narrative structure of the MBN novel is analyzed based on the perspective of Gerard genette's narcissistic theory which focuses the study on one narrative structure, namely the narrative duration. The research method used is a descriptive qualitative approach. Data analysis based on Gerard Genette's theory of naratology uses a hermeneutic technique which includes four stages, namely reading, marking, coding and analyzing. Based on the results of the study found the pattern of the narrative structure of the MBN novel as follows it has two movements, namely a scene and a pause. The scene is a moment when the time of telling is equivalent to the time of the story in the from of dialogue. While  the pause is descriptive data which makes the time of the story zero, but it is still within  the spatial-temporal scope of the story. Key Words: narrative structure, duration sequence, scene, pause